Acculturation of language and culture through manifestation of lexical Usage in cross Indonesian-Malay language - Ery Iswary; Rahim Bin Aman (Fakulti Sains Sosial dan Kemanusiaan, 2011)
This paper discusses how the relationship between language and culture occurs by using linguistic data in Malay and Indonesian languages. It also discusses the form of lexical usage particularly in time and numeral concepts, as well as gender lexicalization in both languages. The data are analysis by using anthropologicallinguistic approach of Kramsch’s theoretical framework that asserted language expresses, enlarges, and symbolizes cultural reality. The theory is affi liated with Sapir-Whorf’s hypothesis that said language relativity and determinism could infl uence human world view. The outcomes of these analysis indicate that language and culture is essential in categorizing the community experience and coding certain name of the reality.